Oxylipins in moss development and defense - de León, Inés Ponce; Hamberg, Mats; Castresana, Carmen (Frontiers in Plant Science, 2015)
Oxylipins are oxygenated fatty acids that participate in plant development and defense against pathogen infection, insects and wounding. Initial oxygenation of substrate fatty acids is mainly catalyzed by lipoxygenases and alpha-dioxygenases but can also take place non-enzymatically by autoxidation or singlet oxygen-dependent reactions. The resulting hydroperoxides are further metabolized by secondary enzymes to produce a large variety of compounds, including the hormone jasmonic acid and short-chain green leaf volatiles. In flowering plants, which lack arachidonic acid, oxylipins are produced mainly from oxidation of polyunsaturated C18 fatty acids, notably linolenic and linoleic acids. Algae and mosses in addition possess polyunsaturated C20 fatty acids including arachidonic and eicosapentaenoic acids, which can also be oxidized by lipoxygenases and transformed into bioactive compounds. Mosses are phylogenetically placed between unicellular green algae and flowering plants, allowing evolutionary studies of the different oxylipin pathways. During the last years the moss Physcomitrella patens has become an attractive model plant for understanding oxylipin biosynthesis and diversity. In addition to the advantageous evolutionary position, functional studies of the different oxylipin-forming enzymes can be performed in this moss by targeted gene disruption or single point mutations by means of homologous recombination. Biochemical characterization of several oxylipin-producing enzymes and oxylipin profiling in P. patens reveal the presence of a wider range of oxylipins compared to flowering plants, including C18 as well as C20-derived oxylipins. Surprisingly, one of the most active oxylipins in plants, jasmonic acid, is not synthesized in this moss. In this review we present an overview of oxylipins produced in mosses and discuss the current knowledge related to the involvement of oxylipin-producing enzymes and their products in moss development and defense.